Pengembangan Instrumen Penilaian Berbantuan Wordwall pada Materi Sistem Koordinasi untuk Siswa Kelas XI IPA - Qurniawan, Muhammad Fani; Nurmawati, Ira; Sahlan, Mohammad (Bioscientist : Jurnal Ilmiah Biologi, 2023)
This research is a type of research and development (Research and Development or R & D) using the ADDIE Branch development model. The aim of this research is to produce a product in the form of a wordwall-assisted assessment instrument on coordination system material for class XI Science students at MA Negeri 2 Jember. The assessment instrument developed contains multiple choice questions (multiple choice) type Higher Order Thinking Skills (HOTS) questions on the coordination system material. The research results show that the validation obtained from experts has been matched with the validation score criteria, material expert validation results are 88.12% (very valid), evaluation expert validation results are 95.55% (very valid), language expert validation results are 86.66 % (very valid), and the results of practitioner validation by teachers were 94.72% (very valid). Meanwhile, the results of student responses were: 1) small scale trial stage 83.17% (very interesting); and 2) large-scale trial phase 85.1% (very interesting). The results of the question item validation test were: 1) 20 of the 25 question items were declared valid with a value of rcount > rtable; 2) the overall reliability value of the questions is 0.792 (high); 3) the level of difficulty of the items in the easy, medium and difficult categories; and 4) the distinguishing power of items in the very good and quite good categories. The wordwall-assisted assessment instrument on the coordination system material was proven to be effective for class 05). Based on the results of this research, it can be concluded that the wordwall-assisted assessment instrument product is categorized as very valid, very practical and effective.